Crime Prevention Through Environmental Design: A Study Of Fear Of Crime And Social Integration Based On Different Road Hierarchy In A Residential Area In Penang, Malaysia - Marzbali, Massoomeh Hedayati (2012)

(untitled)
The concern for environmental safety has led to extensive research on the subject of crime prevention. The influence of Crime Prevention through Environmental Design (CPTED) in reducing crime and fear has found broad theoretical support, but its multivariate predictive relationships have not been empirically validated. This study focuses on the assessment of the CPTED construct that is hypothesized to be a predictor of fear of crime and social integration based on different road hierarchy. Pelbagai penyelidikan mengenai keselamatan persekitaran telah dijalankan akibat kerisauan terhadap isu keselamatan. Pengaruh kaedah Pencegahan Jenayah Melalui Rekabentuk Persekitaran (PJMRBP) di dalam mengurangkan jenayah dan ketakutan terhadap jenayah telah mendapat banyak sokongan dari aspek teoretikal.